The effect of early pregnancy ALT elevation on neonatal birth weight: The mediating role of gestational diabetes mellitus - Wen-Xia Ma; Zhou Xu; Rui Xiao; Xiao-Jun Tang; Li-Juan Fu; Yan-Xiao Xiang; Shao-Min Yu; Yu-Bin Ding; Zhao-Hui Zhong (PLoS ONE, 2025)
Elevated serum alanine aminotransferase (ALT) levels in early pregnancy and gestational diabetes mellitus (GDM) are linked to an increased rate of large for gestational age (LGA) births. Additionally, elevated ALT levels raise the risk of developing GDM, but it remains unclear whether GDM mediates the effect of ALT on neonatal birth weight. This study examines whether GDM mediates this relationship. We conducted a retrospective cohort study with participants from Jinxin Women’s and Children’s Hospital who delivered single live births between 2020 and 2023. A multifactorial logistic regression model assessed the relationship between early pregnancy ALT levels, GDM incidence, and LGA births. A mediation model evaluated GDM’s role in the impact of elevated ALT on neonatal birth weight. Our study included 12,057 patients. After adjusting for confounders, the difference in LGA rates between elevated and normal ALT groups was significant (OR: 1.248, 95% CI: 1.001–1.556, P = 0.049). The GDM incidence difference between these groups was also significant (OR: 1.564, 95% CI: 1.306–1.873, P < 0.01), as was the LGA incidence difference between GDM and non-GDM groups (OR: 1.306, 95% CI: 1.129–1.511, P < 0.01). After adjusting for confounders, we found that elevated ALT levels in early pregnancy and GDM both affected neonatal birth weight. Specifically, elevated ALT levels had a direct impact on neonatal birth weight (β = 0.0291, 95% CI: 0.0100–0.0635), while GDM had an indirect effect (β = 0.0025, 95% CI: 0.0012–0.0056), with GDM accounting for 8.1% of the mediation effect. Our study shows that GDM partly mediates the effect of elevated ALT on neonatal birth weight, highlighting the importance of early ALT and glucose screening in routine prenatal care. Healthcare providers should consider including ALT testing in pregnancy protocols and focus on blood glucose control in patients with elevated ALT to reduce the risk of LGA births.